Analisis Dampak Perubahan Media Promosi Pada Restoran Siap Saji - Aviza Dwi Amalia (Jayapangus Press, 2021)
Utilizing digital media, especially the YouTube platform in advertising, provides convenience and cost savings incurred by business people, including fast-food restaurants such as Pizza Hut, which use the YouTube platform to promote their products, especially in the current Covid-19 pandemic era. The short duration and interesting and unique presentations make it easier for audiences to receive message information conveyed through advertisements. Digital marketing strategy is used because it is easier for producers to influence consumers. With the various conveniences provided by digital media, it certainly makes business people turn to digital media in promoting their products. This paper aims to find out how the impact of the existence of digital media which has experienced a shift from using television is now turning to digital media, especially the YouTube platform as a tool for promotion. Using qualitative methods and literature review. The results of the study with the presence of digital media for shopping advertisements experienced a significant increase in the presence of elements that make it easier for consumers to remember the messages conveyed through advertisements with the repetition of words in each advertisement. With digital media through the YouTube platform, of course, it is very easy considering that the growth of social media users is getting higher day by day